Solar elastosis correlates with high tumor mutation burden and better 5-year disease-specific survival in patients with stage II/III melanoma - Cecilia Lezcano; Li Luo; Ronglai Shen; Irene Orlow; Nancy E. Thomas; Marianne Berwick; Klaus J. Busam (EJC Skin Cancer)
Objective: To evaluate the relation between solar elastosis and tumor mutation burden (TMB) in a large clinically annotated cohort of stage II and III melanoma patients. Methods: Primary cutaneous melanomas from 469 AJCC (8th edition) stage II and III patients with clinical annotation including outcome at 5 years of diagnosis were histopathologically evaluated for solar elastosis. Next-generation sequencing assay MSK-IMPACTTM was employed to determine TMB. Analysis by Fisher’s exact test, chi-square, and Kruskal-Wallis were performed, as well as uni- and multivariate logistic regression. Results: Tumors stratified by low and high TMB showed marked and statistically significant differences in presence and extent of associated solar elastosis. Lower risk patient stage (II versus III by AJCC 8th edition) as well as better 5-year melanomaspecific survival (as binary variable of controls-survivors versus cases-dead of disease at 5 years of diagnosis) were associated with severe solar elastosis. On univariate and multivariate logistic regression models, severe solar elastosis predicted significantly decreased odds of dying of melanoma within 5 years of diagnosis (OR 0.60, 95 % CI 0.39–0.89; and OR 0.42, 95 % CI 0.20–0.83, respectively; both p<0.05) Conclusion: The association of solar elastosis to TMB and 5-year melanoma specific survival points to its potential as a biomarker of clinical relevance that can be assessed by routine histopathology.